Literature Review: Hubungan antara Tingkat Pengetahuan dan Sikap dengan Kejadian Anemia pada Ibu Hamil - Xena Asterina Susilo; Meitria Syahadatina Noor; Triawanti Triawanti; Farida Heriyani; Nur Qamariah (Homeostasis, 2021)
Abstract: Anemia in pregnant women has become an important factor in maternal mortality in Indonesia, especially when bleeding occurs during pregnancy or childbirth. Some literature shows a relationship between knowledge and attitudes with the incidence of anemia in pregnant women. In this literature review, an analysis of the relationship between the level of knowledge and attitudes and the incidence of anemia in pregnant women will be carried out. The review uses the narrative review method. Articles are obtained from keyword searches in the PubMed, Garuda, and Google Scholar databases with the publication range for 2010-2020 in Indonesian or English. A total of 18 articles were analyzed, there were 2,412 subjects of pregnant women studied from various countries. From the search results found 15 articles (83.3%) which indicated that there was a relationship between the level of knowledge and attitudes with the incidence of anemia in pregnant women and 3 (16.6%) articles which indicated that there was no relationship between the level of knowledge and attitudes with the incidence. anemia in pregnant women. The prevalence of anemia in pregnant women is more common in pregnant women who have low knowledge and bad attitudes. Keywords: Knowledge, Attitude, Anemia, Pregnant Women Abstrak: Anemia pada ibu hamil telah menjadi faktor penting dalam kematian ibu di Indonesia, terutama ketika terjadi perdarahan dalam masa kehamilan atau persalinan. Beberapa literatur menunjukkan adanya hubungan diantara pengetahuan dan sikap dengan kejadian anemia pada ibu hamil. Dalam tinjauan literatur ini akan dilakukan analisis mengenai hubungan antara tingkat pengetahuan dan sikap dengan kejadian anemia pada ibu hamil. Tinjauan menggunakan metode narrative review. Artikel diperoleh dari pencarian kata kunci di database PubMed, Garuda, dan Google Scholar dengan rentang publikasi tahun 2010-2020 dalam bahasa Indonesia atau bahasa Inggris. Sebanyak 18 artikel dianalisis, terdapat 2.412 subjek ibu hamil yang diteliti dari berbagai Negara. Dari hasil penelusuran ditemukan 15 artikel (83,3%) yang menunjukkan bahwa terdapat hubungan antara tingkat pengetahuan dan sikap dengan kejadian anemia pada ibu hamil dan 3 (16,6%) artikel yang menunjukkan bahwa tidak terdapat hubungan antara tingkat pengetahuan dan sikap dengan kejadian anemia pada ibu hamil. Prevalensi kejadian anemia pada ibu hamil lebih sering terjadi pada ibu hamil yang memiliki pengetahuan rendah dan sikap yang buruk. Kata-kata Kunci : Pengetahuan, Sikap, Anemia, Ibu Hamil.